Sistem Dashboard Untuk Visualisasi Data Pendapatan dan Pengeluaran Berbasis Web PT. XYZ - Dwi Rio Aryanto; Qori Halimatul Hidayah; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
PT XYZ is a finance company engaged in financing. For controling and cost center project management of each branch, financial reports per branch are required. Currently, there is no financial report per branch at PT XYZ, making it difficult for management to determine policies. The company needs a financial data visualization that presents income and expenditure data per branch. To overcome these problems, an effective, attractive, and multifunctional dashboard system is needed. In developing the dashboard system, using the prototype method. To build a dashboard system, python programming is needed for data processing, and apache superset to build interfaces. The result of the dashboard system development is a system that can process data according to logic allocation and display clear and interesting information. This dashboard system has been implemented so that it can help management in analyzing data and making decisions.